gtAI: an improved species-specific tRNA adaptation index using the genetic algorithm - Anwar, Ali Mostafa; Khodary, Saif M.; Ahmed, Eman Ali; Osama, Aya; Ezzeldin, Shahd; Tanios, Anthony; Mahgoub, Sebaey; Magdeldin, Sameh (Frontiers in Molecular Biosciences, 2023)
The tRNA adaptation index (tAI) is a translation efficiency metric that considers weighted values (Sij values) for codon–tRNA wobble interaction efficiencies. The initial implementation of the tAI had significant flaws. For instance, generated Sij weights were optimized based on gene expression in Saccharomyces cerevisiae, which is expected to vary among different species. Consequently, a species-specific approach (stAI) was developed to overcome those limitations. However, the stAI method employed a hill climbing algorithm to optimize the Sij weights, which is not ideal for obtaining the best set of Sij weights because it could struggle to find the global maximum given a complex search space, even after using different starting positions. In addition, it did not perform well in computing the tAI of fungal genomes in comparison with the original implementation. We developed a novel approach named genetic tAI (gtAI) implemented as a Python package (https://github.com/AliYoussef96/gtAI), which employs a genetic algorithm to obtain the best set of Sij weights and follows a new codon usage-based workflow that better computes the tAI of genomes from the three domains of life. The gtAI has significantly improved the correlation with the codon adaptation index (CAI) and the prediction of protein abundance (empirical data) compared to the stAI.